Evaluasi Pengelolaan Alokasi Dana Desa dalam Upaya Meningkatkan Pembangunan dan Pemberdayaan Masyarakat - Ati Sarlina Maria Tuhana; Akhmad Daerobi; Mulyanto (Penerbit Goodwood, 2022)
Purpose: To find out the effectiveness of the Village Fund Allocation policy in Muke Village, Amabi District, Oefeto Regency, NTT, it is seen from the context, input, process, and product and evaluate the level of the Village Fund Allocation management category Method: Namely quantitative research with a cross sectional approach. Results: Overall these dimensions have a fairly hicross-sectionals scale, namely: The overall context is 79.05 The overall input is 76.10, the overall process is 81.45 and the overall product is 76.88. Limitations: Based on the researcher's direct experience in the research process, there are several limitations, including: The number of respondents is only 33 people, of course, this is still not enough to describe the actual situation and object of research only focuses on the effectiveness of the ADD program in terms of context, input, process, and product as well as the level of management of Village Allocations in the Muke Village category, Amabi District, East Oefeto Regency. NTT. Contribution: For Muke Village, East Amabi Oefeto Region, to make more use of village subsidies and further develop development improvements and community empowerment. For the author or this research to increase knowledge and broaden insight and good experience regarding the problem of managing village fund allocations in an effort to improve community development and empowerment. For the Alma mater, the results of this study are expected to add new references from the analysis of ADD management in improving community development and empowerment.